2018
DOI: 10.2174/1874104501812010060
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, DNA Cleavage and Pharmacokinetic Parameter Study of Substituted Novel Furan C-2 Quinoline Coupled 1, 2, 4-Triazole and Its Analogs

Abstract: Background:Furan, quinoline and triazoles are known for their wide spectrum biologically active molecules. A series of novel furan C-2 quinoline and 1, 2, 4-triazole (FQT) coupled hybrids were designed and synthesized to evaluate for their DNA cleavage and cytotoxic studies.Objectives:In this work we describe the synthesis and biological evaluation of furan C-2 quinoline coupled triazoles exposed for cytotoxic and DNA cleavage study.Methods:The electrophoretic DNA cleavage studies on λ-DNA (Eco-RI/Hinda-III do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One of the group of chemicals are 1,2,4-triazole compounds and drug development studies have been focused on the design and synthesize these compounds due to their clinical importance [15; 24-26]. There are some studies investigating the cytotoxic effects of various compounds containing 1,2,4-triazole on leukemia, lung, prostate, breast, ovary, and colon and melanoma cancer cells [24][25][26][27]. Bekircan et al [14] reported that asymmetric 3,5-diaryl-4H-1,2,4-triazole derivatives have cytotoxic effects on various melanoma cell lines and IC 50 values varied in the range of 6.18-19.6 μM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the group of chemicals are 1,2,4-triazole compounds and drug development studies have been focused on the design and synthesize these compounds due to their clinical importance [15; 24-26]. There are some studies investigating the cytotoxic effects of various compounds containing 1,2,4-triazole on leukemia, lung, prostate, breast, ovary, and colon and melanoma cancer cells [24][25][26][27]. Bekircan et al [14] reported that asymmetric 3,5-diaryl-4H-1,2,4-triazole derivatives have cytotoxic effects on various melanoma cell lines and IC 50 values varied in the range of 6.18-19.6 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Georgiyants et al [24] also demonstrated that the new 1,2,4-triazole (4H) derivatives exhibited cytotoxic effects on melanoma cells at different range. Novel furan C-2 quinoline coupled 1,2,4-triazole analogs were also shown to have a cytotoxic effect on melanoma (A375) cells and the IC 50 values changed between 2.9 and 207.1 µg/mL [26]. 5-mercapto-1,2,4-triazole derivatives exhibited moderate cytotoxic effect on melanoma (A375 and B164A5) cells [25].…”
Section: Resultsmentioning
confidence: 99%
“…Structure of synthesized molecules was drawn by using Chem Draw . Energy minimization protocol and macro molecular force field was used to perform Ligand optimization . Different ligand conformations were produced on the basis of their dihedral energy, bond energy, initial potential energy, CHARM energy values.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic activity of all compounds was studied against A375, MDA-MB 231 cancer cells and HEK293 normal cells using MTT assay. [39,40] Cell lines were obtained from National Centre For Cell Science (NCCS Pune, India), cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum, 2 mmoL/L glutamine, 1% antibiotics solution (100 U/mL penicillin G and 100 mg/mL streptomycin). Cells were grown in 25 cm 2 tissue culture flasks and maintained at 37 C in a humidified incubator with 5% CO 2 .…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…SAR study predicted that halogens at para position of the aldehyde moiety have particular emphasis on the anticancer activity (Scheme 13). [70] Guided by the precedents established in the literature about the therapeutic potentials of hybrid scaffolds, the group of Eman E. Nasr approached the design and synthesis of new quinoline-triazole-chromene derivatives by the fusion of quinoline, triazole and chromene as pharmacophoric units. The desired hybrid analogs were achieved by [3 + 2] cycloaddition, Knoevengel condensation followed by Michael addition reaction.…”
Section: Quinoline-124-triazole Hybridsmentioning
confidence: 99%